THE EFFECT OF TAX TREATY ON FOREIGN DIRECT INVESTMENT IN INDONESIA - Hutomo Nurman Satrio,; Nur Indah Lestari (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2018)
This paper examines the effect of tax treaty, so called Perjanjian Penghindaran Pajak Berganda (P3B), on foreign direct investment inflow to Indonesia in short, middle and long term. From 67 countries that have P3B with Indonesia, we work only with 51 countries because of no longer P3B exist or lack of completed data. Using panel data set of 51 countries from 2000 to 2015 and applying fixed effect model, we find that P3B has insignificant relationship to foreign direct investment inflows in short term. However, tax treaty, both in middle and long term, have a positive relationship on Indonesia’s foreign direct investment inflow with 10%and 1% significant level, respectively. Furthermore, the data show that in all term there are Rp0 foreign direct investment inflow from corresponding countries, which are 58% countries in short terms, 61% in middle term, and 64% in long term. From all those countries that has no investment agreement, majority of them are lower middle income countries. So, Government should evaluate tax treaty that are present and consider more about macroeconomics factor from partner country before signing an agreement.